Virologic and Immunologic Characteristics in Mature Ducks with Acute Duck Hepatitis A Virus 1 Infection - Mao, Sai; Wang, Mingshu; Ou, Xumin; Sun, Di; Cheng, Anchun; Zhu, Dekang; Chen, Shun; Jia, Renyong; Liu, Mafeng; Sun, Kunfeng; Yang, Qiao; Wu, Ying; et al. (Frontiers in Immunology, 2017)
Duck hepatitis A virus 1 (DHAV-1) infection in mature ducks has previously been proposed as a small-animal model for human hepatitis A. However, basic research on the outcome of DHAV-1 infection in mature ducks is limited. Here, we examined the course of viremia, the characteristics of antibody responses, and the profiles of plasma cytokines in mature ducks infected with DHAV-1. During the course of infection, the viremia was detectable soon after infection and persisted for 196 days, however, the ducks presented as clinically asymptomatic. Specific and timely IgG, IgM, and IgA1 responses were elicited. At the same time, extensive inhibition of viral replication was observed with increasing IgG concentration. With respect to pattern recognition receptors, TLR-7 was mainly involved in triggering the innate defense against the DHAV-1 infection. Additionally, plasma immune analytes were measured and were determined to have bidirectional roles in virus clearance. It was concluded that DHAV-1 spreads quickly in blood. The spontaneous clearance of DHAV-1 during asymptomatic infection in mature ducks depends on the cooperation of timely antibody responses and alert innate immune responses. Moreover, the delayed clearance may be associated with a weak IFN-γ-producing CD8+ T cell response. This study allows us to reveal the mechanism of clearance and persistence of DHAV-1 infection in mature ducks. We anticipate that it will provide a basis for future studies focused on defining the nature mechanisms involved in the clearance and persistence of human hepatitis virus.